Observational study on the palatability and tolerability of oral prednisolone and oral dexamethasone in children in Saudi Arabia and the UK - Aljebab, Fahad; Alanazi, Mofadhi; Choonara, Imti; Conroy, Sharon (BMJ, 2017)
Background: Short-course oral corticosteroids are routinely used to treat acute asthma and croup. We evaluated their tolerability and palatability in Saudi Arabian (SA) and UK children. Methods: Prospective observational/interview study (three months in each country). Palatability was evaluated using a five-point facial scale and tolerability by direct questioning of patient/parents. Results: In SA, of 122 patients (2–10years) recruited: 52 received prednisolone base tablets; 37 prednisolone sodium phosphate syrup; 33 dexamethasone elixir. In the UK, of 133 patients (2–16years): 38 received prednisolone base tablets (mainly crushed and dispersed); 42 prednisolone sodium phosphate soluble tablets; 53 dexamethasone sodium phosphate oral solution. In both countries dexamethasone had the highest palatability scores (SA mean: 1.97; UK mean: 3) and prednisolone base tablets the lowest (SA mean: 1.12; UK mean: 1.39). Palatability scores improved for all formulations of prednisolone with each subsequent daily dose. In SA prednisolone base tablets were associated with more nausea (24 vs 7 patients) and vomiting (5 vs 0) than sodium phosphate syrup (P=0.008 and P=0.073 respectively). In the UK vomiting occurred more frequently with prednisolone base (8) than sodium phosphate soluble tablets (2) (P=0.041). In both centres dexamethasone was associated with less side effects. Vomiting (1 vs 0 patients), nausea (7 vs 3) and abdominal pain (10 vs 8) occurred more with dexamethasone sodium phosphate solution than dexamethasone elixir. Conclusions: Dexamethasone sodium phosphate solution was the most palatable preparation. Prednisolone base tablets were rated least palatable and were least well tolerated. Palatability scores improved with each dose taken.